Representation for Genetic and Evolutionary Algorithms: Studies in Fuzziness and Soft Computing - Rigelsford, Jon (Industrial robot, 2003)
Representation for Genetic and Evolutionary Algorithms: Studies in Fuzziness and Soft Computing, by F. Rothlauf, is reviewed.